An initial review of residual symptoms after empirically supported trauma-focused cognitive behavioral psychological treatment. (April 2019) - Larsen, Sadie E.; Bellmore, Aimee; Gobin, Robyn L.; Holens, Pamela; Lawrence, Karen A.; Pacella-LaBarbara, Maria L.
Highlights: The PSTD psychosocial treatment literature does not often examine residual symptoms. We examined residual PTSD and secondary symptoms in RCTs of empirically supported treatments. Most studies had evidence of at least subthreshold residual PTSD symptoms. Two thirds of studies had residual symptoms of associated comorbidities. Abstract: Objective: Although residual symptoms remain following clinical treatment for posttraumatic stress disorder (PTSD), little is known about the characteristics of these residual symptoms. We aimed to determine the type, severity, and frequency of symptoms that remain after trauma-focused psychotherapy. Methods: We conducted a systematic review of 51 randomized controlled trials of empirically supported psychosocial interventions for PTSD (68 total treatment arms). Outcomes included: 1) PTSD symptoms and 2) conditions commonly comorbid with PTSD: depression, anxiety, and quality of life impairment. Results: In general, the results revealed that participants who completed PTSD treatment continued to report residual PTSD symptoms: 31% reported clinical symptom levels, and 59% reported subthreshold levels at posttreatment, particularly within the hyperarousal cluster. Residual symptoms also emerged for depression (19% clinical), anxiety (55% clinical), and quality of life (36% clinical). Few differences emerged across treatment types, but differential patterns were revealed for sample/trauma types. Conclusions: Results suggest a need for focused research attention to and clinical assessment of individual residual symptoms following empirically supported treatment for PTSD to determine whether further treatment sessions are warranted.